IMPLEMENTATION OF COOPERATIVE LEARNING MODEL STAD-TYPE AS AN EFFORT TO IMPROVE STUDENT ACTIVITY AND OUTCOMES IN MATHEMATICS ON FUNCTIONAL LIMITS MATERIAL - Dewi Siti Marwah; Wiwit Damayanti Lestari; Misbahussurur Misbahussurur (Indonesian Journal of Educational Development (IJED), 2023)
This study aims to determine whether learning using the cooperative learning model of Student Team Achievement Division (STAD) type can increase student activity and learning outcomes in limit function material or not. This study is a Classroom Action Research (CAR) conducted at MA Negeri 1 Indramayu. The subjects in this study were 26 students of class XI MIPA 1. The instruments used in this research were observation sheets of student learning activity given each cycle to assess student activity and formative tests given each cycle to measure learning outcomes improvement. The results of processing student activity data obtained the percentage of activity in cycle I 69.23%, cycle II 84.62%, and cycle III 92.31%. Likewise, data on student learning outcomes obtained an average of cycle I 48.08, cycle II 75.96, and cycle III 84.04. Furthermore, it was obtained data on an increase in the number of students who achieved learning mastery, they are in cycle I as many as 5 students out of 26 students or 19% with very low mastery criteria, in cycle II as many as 21 students out of 26 students or 81% with very high mastery criteria, and in cycle III as many as 24 students or 92% with very high mastery criteria.